1989
DOI: 10.1677/joe.0.1210299
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the glycogenolytic gluconeogenetic hormones, glucagon, vasopressin and angiotensin II, on biliary excretion of iodothyronines in rats is possibly related to the inhibition of 5′-monodeiodination in the liver

Abstract: Polyethylene tubes were inserted into the bile duct and femoral vein of rats under pentobarbital anaesthesia and bile was collected for three 2-h periods. After the first (control) period the animals were infused intravenously at a rate of 1.2 ml/h with the following compounds: (1) 0.9% (w/v) NaCl (control group), (2) glucagon (1200 ng/h), (3) vasopressin (1200 ng/h) or (4) angiotensin II (600 ng/h). The concentrations of thyroxine (T4), tri-iodothyronine (T3) and reverse tri-iodothyronine (rT3) in the bile we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
(16 reference statements)
2
6
0
Order By: Relevance
“…Alternatively, interference of binding of thyroid hormones to thyroid binding globulin may contribute to lowering of concentrations of both T4 and T3 with a rise in T3 resin uptake (Afandi et al, 2000;Chopra et al, 1986;Oppenheimer et al, 1982;Chopra et al, 1979). Finally, the inhibition of the deiodinase as well as impaired hypothalamic pituitary axis with lowering of circulating TSH concentration have been attributed to rising stress hormones i.e., catecholamines, glucocorticoid, and glucagon (Duntas et al, 1999;Langer et al, 1989;Hidal and Kaplan, 1988;Kabadi and Premachandra, 1988;Langer and Foldes, 1988;Bianco et al, 1987;Faber et al, 1987;Kabadi and Premachandra, 1987;Silva and Larsen, 1986;Chopra et al, 1985;Langer et al, 1985;Kabadi et al, 1982). These hormones also appear to play a role in the interference in binding between thyroid hormones and their binding globulin attributed to elevation of circulating free fatty acids by promoting lipolysis (Afandi et al, 2000;Faber et al, 1987;Chopra et al, 1986;Chopra et al, 1985;Oppenheimer et al, 1982;Chopra et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, interference of binding of thyroid hormones to thyroid binding globulin may contribute to lowering of concentrations of both T4 and T3 with a rise in T3 resin uptake (Afandi et al, 2000;Chopra et al, 1986;Oppenheimer et al, 1982;Chopra et al, 1979). Finally, the inhibition of the deiodinase as well as impaired hypothalamic pituitary axis with lowering of circulating TSH concentration have been attributed to rising stress hormones i.e., catecholamines, glucocorticoid, and glucagon (Duntas et al, 1999;Langer et al, 1989;Hidal and Kaplan, 1988;Kabadi and Premachandra, 1988;Langer and Foldes, 1988;Bianco et al, 1987;Faber et al, 1987;Kabadi and Premachandra, 1987;Silva and Larsen, 1986;Chopra et al, 1985;Langer et al, 1985;Kabadi et al, 1982). These hormones also appear to play a role in the interference in binding between thyroid hormones and their binding globulin attributed to elevation of circulating free fatty acids by promoting lipolysis (Afandi et al, 2000;Faber et al, 1987;Chopra et al, 1986;Chopra et al, 1985;Oppenheimer et al, 1982;Chopra et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…At a day of experiment polyethylene tubings were inserted into a bile duct and femoral vein under pentobarbital anesthesia. The bile was then continuously collected into preweighed vials containing methimazole and I or 2 h samples were taken for radioimmunoassay of T4, T3 and rT3 as previously described (Langer et al, 1988(Langer et al, , 1989. In Experiment 1 two groups of 7 rats each were used.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous experiments (Langer et al, 1988(Langer et al, , 1989 we suggested that the acute increase in biliary excretion of rT3 reflected the acute inhibition of 5'deiodinase type Tin the liver and thus it may be employed as a useful marker of the activity of that enzyme in vivo. The aim of this study was to test this hypothesis with the aid of PTU.…”
Section: Experimental and Clinical Endocrinologymentioning
confidence: 98%
“…Exogenous administration of hormones that counterregulate hypoglycemia acutely increases biliary rT3 excretion (5)(6)(7). In the present study we have evaluated the effect of endogenous counter-regulatory hormones whose secretion was stimulated by acute insulininduced hypoglycemia to expand these studies.…”
Section: Bratislava Slovakiamentioning
confidence: 99%
“…conjugated plus unconjugated) rT3 was estimated by an in-house RIA (8) that later was modified slightly by using smaller aliquots of bile for individual estimations (6). The sensitivity of the assay is less than 0.5µg/mI.…”
Section: Radioimmunoassay Of Rt^i N Bilementioning
confidence: 99%